Leaking stoppage cement paste with high acid dissolution rate and preparation method thereof
By using plugging cement slurry with high acid dissolution rate in low-permeability oil and gas reservoirs, the problem of low acid dissolution rate of cement stone in the existing technology is solved, the rapid dissolution of cement stone and the restoration of formation fluid flow channels are achieved, which improves the Production of oil and gas reservoirs.
Patent Information
- Application Number
- CN202411176623.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-26
- Publication Date
- 2025-01-21
AI Technical Summary
In the prior art, it is difficult to effectively remove crushed cement chips in the holes and cement rings around the holes in the low-permeability oil and gas reservoirs, resulting in a decrease in the exposed area of the production layer and a decrease in the production capacity of the oil and gas well.
Develop a high -acid -soluble rate blocked cement slurry. By adding acid -soluble pellets, acid -soluble hard fillers, enhanced agents, solvents, water loss and slowing agents to the cement slurry, forming an excellent plugging The cement slurry system of sex, high strength and high -acid solution rate.
This cement slurry system can effectively dissolve cement stone, quickly restore formation fluid flow channels, increase the production of oil and gas reservoirs, and solve the problem of low productivity of single wells in low-permeability oil and gas reservoirs.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of petroleum engineering cementing, and in particular to a plugging cement slurry with a high acid dissolution rate and a preparation method thereof. Background Art
[0002] There are still a large number of low-permeability oil and gas reservoirs in my country that are waiting to be developed. An important reason for this phenomenon is the completion method of low-permeability oil and gas fields in the engineering community. The main reason for supporting the perforation completion method is that it is believed that this completion method can effectively carry out stratified production and is conducive to the adoption of stratified enhanced production methods such as acidizing and fracturing. However, the use of acidizing treatment after perforation cannot effectively remove the broken cement stone chips in the holes and dissolve the cement ring around the holes, which reduces the exposed area of the production layer and leads to a decrease in the production capacity of the oil and gas wells; the main reason for supporting the open hole completion method is that the porosity, permeability and original oil and gas outflow capacity of the oil-bearing rocks in the low-permeability oil and gas reservoirs are low. Due to the contamination of the oil layer by cement slurry and the further sealing of the oil rock surface by dense cement stone, even if the high-porosity perforation method is used, the perforation hole area of the unit length of the oil layer section only accounts for 0.5-1.0% of the surface area of the rock in this section, which will affect the oil and gas outflow capacity and single well production capacity; in addition, whether it is a sandstone oil and gas reservoir or a limestone oil and gas reservoir, it usually must be acidified before it can be put into production. It can be seen that exploring effective technical means to improve the single-well productivity of low-permeability oil and gas reservoirs is one of the practical production problems that urgently need to be solved in the current domestic oil and gas field development.
[0003] The cement paste formed by the conventional plugging cement slurry system has low porosity and permeability. The contact area between the acid and the cement paste particles is small, and it is difficult for the acid to enter the pores of the cement paste, resulting in a low acid dissolution rate of the cement paste, which in turn affects the acid dissolution rate.
[0004] In the gas storage wells in Liaohe area, the reservoir has a vicious leakage. If conventional oil well cement slurry is used for isolation, it will cause damage to the reservoir. The acid dissolution effect of conventional cement sheath is poor, and the reservoir flow capacity recovers slowly during the later acidification process. In order to restore the flow channel of the reservoir fluid, the plugged cement stone should have strong acid solubility and be able to restore the flow channel of the formation fluid as soon as possible during the later acidification process.
[0005] Since the hydrate of silicate cement has a certain acid solubility in acid solution, it must be supplemented with other filling materials, dissolving agents and various treatment agents in application. By optimizing the cement base material and filling materials, dissolving agents and treatment agents, and evaluating the comprehensive construction performance, a cement slurry system with a strong acid solubility rate is developed to maximize the acid solubility of cement stone, so as to achieve the purpose of protecting the reservoir and restoring the channel for the flow of reservoir fluid. Therefore, the development of a cement slurry system with strong acid solubility is of great significance to protecting the reservoir. Summary of the invention
[0006] One of the purposes of the present invention is to provide a plugging cement slurry with a high acid dissolution rate.
[0007] The second object of the present invention is to provide a method for preparing the high acid-dissolving rate plugging cement slurry.
[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0009] In a first aspect, the present invention provides a high acid-dissolving rate plugging cement slurry, comprising the following components in parts by weight: 100 parts of oil well silicate cement, 8-20 parts of acid-soluble plugging particles, 30-50 parts of acid-soluble hard fillers, 5-10 parts of reinforcing agents, 0.1-0.3 parts of accelerators, 4-6 parts of fluid loss reducers, 0.5-1 parts of retarders, and 50-70 parts of water;
[0010] Among them, the solubilizing agent is dodecyl sulfate;
[0011] The acid-soluble plugging particles are fillers with a particle size of 10-20 mesh;
[0012] The acid-soluble hard filler is composed of fillers of three different particle sizes in the following weight proportions: 4.4 to 7.2 parts of 325 mesh, 20 to 33.4 parts of 600 mesh, and 5.6 to 9.4 parts of 3000 mesh.
[0013] The following is a detailed description:
[0014] In some embodiments, the oil well silicate cement is one or more of grade A, grade G and grade H, preferably grade G silicate cement.
[0015] The grade of the oil well silicate cement is defined according to GB10238-98 standard.
[0016] The weight proportion of oil well silicate cement is 100 parts.
[0017] In some embodiments, the acid-soluble plugging particles are calcium carbonate or magnesium carbonate with a particle size of 10-20 meshes.
[0018] Typical but non-limiting weight portions of the acid-soluble plugging particles are, for example, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, and 20 parts.
[0019] In some embodiments, the acid-soluble hard filler is calcium carbonate or magnesium carbonate.
[0020] The present invention adopts three kinds of acid-soluble hard fillers (such as calcium carbonate): 325 mesh, 600 mesh and 3000 mesh. The three kinds of calcium carbonate are composed according to the following weight proportions: 4.4-7.2 parts, 20-33.4 parts of 600 mesh and 5.6-9.4 parts of 3000 mesh.
[0021] Typical but non-limiting weight portions of acid-soluble hard fillers are, for example, 30, 32, 35, 36, 38, 40, 42, 45, 46, 48, and 50 parts, among which typical but non-limiting weight portions of 325 mesh fillers are, for example, 4.5, 4.6, 4.8, 5.0, 5.2, 5.4, 5.6, 6, 6.5, 6.6, 6.8, 7, and 7.2 parts, typical but non-limiting weight portions of 600 mesh fillers are, for example, 20, 21.5, 22, 24, 26, 28, 30, 32, and 33.4 parts, and typical but non-limiting weight portions of 3000 mesh fillers are, for example, 5.6, 6, 7, 8, 9, and 9.4 parts.
[0022] In some embodiments, the reinforcing agent is calcium oxide or magnesium oxide. Typical but non-limiting weight portions of the reinforcing agent are, for example, 5, 6, 7, 8, 9, or 10 parts.
[0023] In some embodiments, the dissolution agent is sodium dodecyl sulfate or ammonium dodecyl sulfate. Typical but non-limiting weight parts of the dissolution agent are, for example, 0.1, 0.2, or 0.3 parts.
[0024] The present invention selects dodecyl sulfate for physical foaming to generate homogeneous bubbles capable of withstanding pressure, thereby achieving the effect of significantly improving the acid dissolution rate. Similar effects cannot be achieved by using other reagents.
[0025] In some embodiments, the fluid loss agent is a vinyl polymer, preferably polyvinyl alcohol. Typical but non-limiting weight parts of the fluid loss agent are, for example, 4, 5, or 6 parts.
[0026] In some embodiments, the retarder is an acrylamide polymer. Typical but non-limiting weight portions of the retarder are, for example, 0.5, 0.6, 0.7, 0.8, 0.9, or 1 part.
[0027] In some embodiments, the water is deionized water. Typical but non-limiting weight portions of deionized water are, for example, 50, 52, 55, 56, 58, 60, 62, 65, 66, 68, and 70 parts.
[0028] In a second aspect, the present invention provides a method for preparing a high acid-dissolving rate plugging cement slurry, comprising the following steps:
[0029] The oil well silicate cement, the acid-soluble plugging particles, the acid-soluble hard filler (325 mesh acid-soluble hard filler, 600 mesh acid-soluble hard filler and 3000 mesh acid-soluble hard filler), the reinforcing agent and the dissolving agent are mixed uniformly to obtain a dry powder;
[0030] Stir water, fluid loss reducer and retarder at low speed to form a mixed liquid;
[0031] Add the dry powder into the mixed liquid, cover the mixer lid, and stir at high speed to obtain leak-proof cement slurry with a high acid solubility rate.
[0032] In some embodiments, the low-speed stirring speed is 4000 rpm±200 rpm, and the stirring time is 2-3 minutes.
[0033] In some embodiments, the high-speed stirring speed is 12000 rpm±500 rpm, and the stirring time is 45-60 s.
[0034] Beneficial effects:
[0035] The present invention adjusts the proportions and types of plugging particles, dissolving agents, reinforcing agents, etc. and adopts acid-soluble fillers of different particle sizes to match each other, so that the obtained cement slurry system has excellent plugging performance, high strength, high acid dissolution rate and acid solubility, and is used for cementing construction of natural fracture leakage formations. During the construction process, the cement slurry plays a certain plugging function, and the intrusion distance of the part of the cement slurry entering the formation does not exceed 10 cm; after the cement slurry solidifies, the cement slurry entering the near-well wall can be dissolved through the acid washing process, so as to achieve the purpose of rapid formation unblocking, open up the oil and gas seepage channel, and provide a basic guarantee for increasing the output of oil and gas reservoirs.
[0036] The present invention has been described in detail above, but the above embodiments are only illustrative in nature and are not intended to limit the present invention. In addition, this article is not limited by any theory described in the above prior art or invention content or the following examples. DETAILED DESCRIPTION
[0037] The present invention is further described below in conjunction with examples. It should be noted that the following examples are provided for illustrative purposes only and do not constitute a limitation on the scope of protection claimed for the present invention.
[0038] Unless otherwise specified, the raw materials, reagents, methods, etc. used in the examples are conventional raw materials, reagents, methods in the art.
[0039] Oil well silicate grade G cement comes from Dalian Cement Group Co., Ltd.;
[0040] The fluid loss reducer used in the embodiment is polyvinyl alcohol, which comes from the cementing company of Changcheng Drilling Engineering Co., Ltd.;
[0041] The retarder used in the embodiment is acrylamide polymer, which is GWR-100L retarder from the cementing company of Great Wall Drilling Engineering Co., Ltd.;
[0042] The reinforcing agent used in the embodiment is magnesium oxide, which is from Yingkou Lixin Magnesium Industry Co., Ltd.
[0043] The dissolution agent used in the examples is sodium dodecyl sulfate.
[0044] Example 1
[0045] Weigh 100 parts of oil well silicate grade G cement, 8 parts of 10 mesh calcium carbonate plugging particles, 40 parts of calcium carbonate (wherein the amounts of 325 mesh, 600 mesh, and 3000 mesh calcium carbonate are 5.8 parts, 26.6 parts, and 7.6 parts, respectively), 6 parts of reinforcing agent, 0.2 parts of solubilizing agent, 5 parts of fluid loss additive, 0.7 parts of retarder, and 65 parts of deionized water.
[0046] The preparation method of leak-proof acid-soluble cement slurry comprises the following steps:
[0047] Weigh oil well silicate grade G cement, calcium carbonate plugging particles, 325 mesh calcium carbonate, 600 mesh calcium carbonate, 3000 mesh calcium carbonate, enhancer, and solvent promoter, mix well to obtain dry powder;
[0048] Measure water, stir water, fluid loss reducer and retarder at low speed (4000r / min) for 2 minutes to form a mixed solution, slowly add the mixed dry powder into the mixed solution, cover the mixer lid, and stir at high speed (12000r / min) for 45s.
[0049] Example 2
[0050] Weigh 100 parts of oil well silicate grade G cement, 12 parts of 10 mesh calcium carbonate plugging particles, 40 parts of calcium carbonate (wherein the amounts of 325 mesh, 600 mesh, and 3000 mesh calcium carbonate are 5.8 parts, 26.6 parts, and 7.6 parts, respectively), 6 parts of reinforcing agent, 0.2 parts of solubilizing agent, 5 parts of fluid loss additive, 0.7 parts of retarder, and 65 parts of deionized water.
[0051] The preparation method is the same as that of Example 1.
[0052] Example 3
[0053] Weigh 100 parts of oil well silicate grade G cement, 16 parts of 10 mesh calcium carbonate plugging particles, 40 parts of calcium carbonate (wherein the amounts of 325 mesh, 600 mesh, and 3000 mesh calcium carbonate are 5.8 parts, 26.6 parts, and 7.6 parts, respectively), 6 parts of reinforcing agent, 0.2 parts of solubilizing agent, 5 parts of fluid loss additive, 0.7 parts of retarder, and 65 parts of deionized water.
[0054] The preparation method is the same as that of Example 1.
[0055] Example 4
[0056] Weigh 100 parts of oil well silicate grade G cement, 20 parts of 10 mesh calcium carbonate plugging particles, 40 parts of calcium carbonate (wherein the amounts of 325 mesh, 600 mesh, and 3000 mesh calcium carbonate are 5.8 parts, 26.6 parts, and 7.6 parts, respectively), 6 parts of reinforcing agent, 0.2 parts of solubilizing agent, 5 parts of fluid loss additive, 0.7 parts of retarder, and 65 parts of deionized water.
[0057] The preparation method is the same as Example 1.
[0058] Example 5
[0059] Weigh 100 parts of oil well silicate grade G cement, 16 parts of 10 mesh calcium carbonate plugging particles, 50 parts of calcium carbonate (wherein the amounts of 325 mesh, 600 mesh, and 3000 mesh calcium carbonate are 7.2 parts, 33.3 parts, and 9.5 parts, respectively), 6 parts of reinforcing agent, 0.2 parts of solubilizing agent, 5 parts of fluid loss additive, 0.7 parts of retarder, and 68.2 parts of deionized water.
[0060] The preparation method is the same as Example 1.
[0061] Example 6
[0062] The difference between this embodiment and embodiment 1 is that the amount of the solvent added is 0.1 parts.
[0063] Example 7
[0064] The difference between this embodiment and embodiment 1 is that the amount of the solvent added is 0.3 parts.
[0065] Comparative Example 1
[0066] The difference between this comparative example and Example 1 is that the amount of the solvent added is 0.
[0067] Comparative Example 2
[0068] The difference between this comparative example and Example 1 is that the amount of the solvent added is 0.5 parts.
[0069] Comparative Example 3
[0070] The difference between this comparative example and Example 1 is that the dissolution agent is replaced by sodium dodecylbenzenesulfonate.
[0071] Comparative Example 4
[0072] The difference between this comparative example and Example 1 is that the amount of 10-mesh calcium carbonate plugging particles added is 2 parts.
[0073] Comparative Example 5
[0074] The difference between this comparative example and Example 1 is that the amount of calcium carbonate used is 40 parts, wherein the amounts of 325 mesh, 600 mesh, and 3000 mesh calcium carbonate are applied on average, namely 13.3 parts, 13.3 parts, and 13.3 parts, respectively.
[0075] The key performance tests of the cement slurry system were carried out on the examples and comparative examples at 60°C and 140°C respectively:
[0076] 1. Acid dissolution rate:
[0077] Place the cement slurry in a cylindrical mold of Φ25.4mm×50.8mm, and place the mold in a high-temperature and high-pressure curing kettle. Set the curing temperature to 60℃~140℃, the curing pressure to 20MPa, and the curing time to 24h.
[0078] After the curing is completed, the mold is disassembled and a cement stone cylindrical specimen is prepared. The cement stone cylindrical specimen is dried and weighed, and the mass is recorded as m1.
[0079] Place the cement stone cylindrical specimen into a high-temperature acid-soluble cup (similar to a pressure cooker, made of polytetrafluoroethylene, cylindrical in shape, with an inner diameter of 80 mm and an inner height of 80 mm, so that the volume ratio of the high-temperature acid-soluble cup to the cement stone cylindrical specimen is 16:1, and its wall thickness is 15 mm, and the end face is sealed with an O-ring, so that the high-temperature acid-soluble cup can withstand a pressure of 200°C and 5MPa). Prepare 12% hydrochloric acid, and fill the high-temperature acid-soluble cup with the cement stone cylindrical specimen with the 12% hydrochloric acid. Place an O-ring on the top of the high-temperature acid-soluble cup, cover the cup lid tightly, and place it in the oven.
[0080] Heat the oven to the experimental temperature of 60℃~140℃. After t hours of acid dissolution, disassemble the high-temperature acid dissolution cup, take out the cement stone debris after acid dissolution, rinse it with clean water, dry it, weigh it and record the mass as m2.
[0081] The acid solubility rate η was calculated according to the following formula:
[0082]
[0083] For different acid dissolution times, such as 0..5h, 1h, 1.5h, 2h, different acid dissolution rates can be obtained, and the acid dissolution rate Φ can be calculated by the following formula:
[0084] Φ(% / h)=η / t,
[0085] The present invention adopts the acid dissolution rate under the same time to characterize the speed of acid dissolution of cement stone under different solvent addition conditions.
[0086] 2. Leakage plugging performance:
[0087] The plugging performance test was carried out using a cement slurry dynamic crack plugging instrument. The test method was as follows: adjust the annular gap between the plugging instrument kettle and the cone so that the annular gap width reaches 1mm-2mm. At this time, fix the relative maximum position of the kettle and the cone, and push the cone to the bottom so that the annular gap width between the cone and the kettle is 0mm; preheat the plugging instrument to a certain temperature. If the experimental test temperature is below 95°C, the preheating temperature is the experimental test temperature. If the experimental test temperature is above 95°C, the preheating temperature is 95°C. After the preheating is completed, place the cement slurry in the plugging instrument kettle. Inside the kettle, record the introduced volume as V1, and maintain the cement slurry for 10 minutes to allow the cement slurry to be evenly heated to the experimental temperature; slowly open the air inlet to slowly increase the pressure on the cement slurry surface in the kettle. When the pressure reaches 0.1MPa, push the cone down to the bottom. At this time, the annular gap width between the kettle and the cone is 1mm-2mm as set before, and continue to slowly increase the air pressure on the liquid surface until the experimental pressure reaches 4MPa-6MPa; after 5 minutes, the experiment is over, the pressure and temperature in the kettle are reduced, the liquid storage tank is opened, and the volume of cement slurry V2 in the liquid storage tank is measured.
[0088] The plugging rate μ is calculated according to the following formula:
[0089]
[0090] The higher the plugging rate, the stronger the plugging performance of the cement slurry.
[0091] 3. Compressive strength:
[0092] Place the cement slurry in a cubic mold of 50.8mm×50.8mm×50.8mm, and place the mold in a high-temperature and high-pressure curing kettle. Set the curing temperature to 60℃~140℃, the curing pressure to 20MPa, and the curing time to 24h.
[0093] After the curing is completed, the mold is disassembled and cement stone cube specimens are prepared.
[0094] The compressive strength of cement stone cube specimens was tested using a universal material testing machine.
[0095] The results are shown in Table 1 and Table 2:
[0096] Table 1 Key properties of cement slurry at 60℃
[0097]
[0098]
[0099] Table 2 Key properties of cement slurry at 140℃
[0100]
[0101] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents, without departing from the spirit and essence of the claims of the present invention; and these modifications or replacements are still within the scope defined by the claims of the present invention.
Claims
1. A high acid dissolution rate plugging cement slurry, characterized in that: The invention comprises the following components in parts by weight: 100 parts of oil well silicate cement, 8-20 parts of acid-soluble plugging particles, 30-50 parts of acid-soluble hard filler, 5-10 parts of reinforcing agent, 0.1-0.3 parts of dissolving agent, 4-6 parts of fluid loss reducing agent, 0.5-1 parts of retarder, and 50-70 parts of water; Among them, the solubilizing agent is dodecyl sulfate; The acid-soluble plugging particles are fillers with a particle size of 10-20 mesh; The acid-soluble hard filler is composed of fillers of three different particle sizes in the following weight proportions: 4.4 to 7.2 parts of 325 mesh, 20 to 33.4 parts of 600 mesh, and 5.6 to 9.4 parts of 3000 mesh.
2. The high acid-soluble plugging cement slurry according to claim 1, characterized in that: The oil well silicate cement is one or more of grade A, grade G and grade H, preferably grade G silicate cement.
3. The high acid-soluble plugging cement slurry according to claim 1, characterized in that: The reinforcing agent is calcium oxide or magnesium oxide.
4. The high acid-soluble plugging cement slurry according to claim 1, characterized in that: The dissolution promoter is sodium dodecyl sulfate or ammonium dodecyl sulfate.
5. The high acid-soluble plugging cement slurry according to claim 1, characterized in that: The fluid loss reducer is an ethylene polymer, preferably polyvinyl alcohol.
6. The high acid-dissolving rate plugging cement slurry according to claim 1, characterized in that: The retarder is acrylamide polymer.
7. A method for preparing the acid-soluble cement slurry according to any one of claims 1 to 6, characterized in that: The following steps are involved: The oil well silicate cement, the acid-soluble plugging particles, the acid-soluble hard filler (325 mesh acid-soluble hard filler, 600 mesh acid-soluble hard filler and 3000 mesh acid-soluble hard filler), the reinforcing agent and the dissolving agent are mixed uniformly to obtain a dry powder; Stir water, fluid loss reducer and retarder at low speed to form a mixed liquid; Add the dry powder into the mixed liquid, cover the mixer lid, and stir at high speed to obtain leak-proof cement slurry with a high acid solubility rate.
8. The preparation method according to claim 7, characterized in that: The low-speed stirring speed is 4000±200r / min, and the stirring time is 2-3min.
9. The preparation method according to claim 7, characterized in that: The high-speed stirring speed is 12000±500r / min, and the stirring time is 45-60s.